1972
DOI: 10.1017/s0022172400022579
|View full text |Cite
|
Sign up to set email alerts
|

The serum and conjunctival antibody response to trachoma in Gambian children

Abstract: SUMMARYNinety-nine young Gambian children were studied for 61 weeks. About half of them had trachoma at the outset, and 80 % of the remainder acquired the disease while under observation. IgG trachoma antibody in the serum and IgG and IgA antibodies in the conjunctival secretions (CS) were titrated by an indirect immunofluorescence method. In serum samples obtained in capillary tubes the mean titre was slightly higher than in samples collected on filter paper. Serum antibody at titres > 1/10 was invariably ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Their proposal was based on the finding of a high prevalence of antichlamydial IgG antibody in ocular secretions from children with active trachoma, and the fact that higher titres of antichlamydial IgG antibody were found in serum and tears from isolation positive than isolation negative subjects [10][11][12]. On the other hand, ocular secretions from children with trachoma showed neutralizing activity in the owl monkey model [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their proposal was based on the finding of a high prevalence of antichlamydial IgG antibody in ocular secretions from children with active trachoma, and the fact that higher titres of antichlamydial IgG antibody were found in serum and tears from isolation positive than isolation negative subjects [10][11][12]. On the other hand, ocular secretions from children with trachoma showed neutralizing activity in the owl monkey model [8].…”
Section: Discussionmentioning
confidence: 99%
“…Barenfanger demonstrated that neutralization was mediated in this case by immunoglobulin [9]. Others have found a positive correlation between anti-chlamydial antibody levels and the presence of chlamydia in the conjunctiva of individuals in trachoma endemic communities; indeed the presence of such antibodies has been used as a diagnostic marker of active trachoma [10][11][12].…”
Section: Introductionmentioning
confidence: 97%
“…One technique was the inclusion antigen (inclusion-IF) test originally used by Collier et al (1) and refitted by Richmond and Caul (4). Here intact chlamydial inclusi~ons in cell monolayers are used as antigen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wang (1971) has devised a micro-immunofluorescent (IF) procedure which is type-specific and has the further advantage that individual immunoglobulins such as IgM can be measured. Similar immunofluorescent techniques have been used by Hanna, Jawetz, Nabli, Hoshiwara, Ostler, and Dawson, (1972) and by Collier, Sowa, and Sowa (1972) to assay antibodies in the sera of patients with trachoma, with good correlation between antibody levels and clinical disease.…”
mentioning
confidence: 91%